2016
DOI: 10.3393/ac.2016.32.6.215
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Left Colon Cancer Should Be Managed by Using a Subtotal Colectomy Instead of Colonic Stenting

Abstract: PurposeThis study compared a subtotal colectomy to self-expandable metallic stent (SEMS) insertion as a bridge to surgery for patients with left colon-cancer obstruction.MethodsNinety-four consecutive patients with left colon-cancer obstruction underwent an emergency subtotal colectomy or elective SEMS insertion between January 2007 and August 2014. Using prospectively collected data, we performed a retrospective comparative analysis on an intention-to-treat basis.ResultsA subtotal colectomy and SEMS insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Other studies have reported synchronous cancer in 3%-11% of patients who undergo PA for left-sided colon cancer [15,16]. PA might be an oncologically safe strategy for patients with synchronous tumor [13].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other studies have reported synchronous cancer in 3%-11% of patients who undergo PA for left-sided colon cancer [15,16]. PA might be an oncologically safe strategy for patients with synchronous tumor [13].…”
Section: Discussionmentioning
confidence: 88%
“…However, colonic stent has several disadvantages such as perforation, re-obstruction, and stent migration [11,12]. Technical and clinical failure rates of colonic SEMS are 20%-30% [13]. A randomized controlled trial has reported a technical failure rate of 53.3% [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Min et al, reported that the mean hospital stay was 12 days (range 10-15 days). 10 Andreano et al, showed that all patients with a regular postoperative course have had no more than 10 days of hospitalization except for those who suffered postoperative ileus which solved after no more 15 days. 11 In this study, 90% of cases had adenocarcinoma and 10% had mucinous adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A subtotal colectomy can treat synchronous tumors in the proximal colon, reduce total hospital stays, and avoid oncologic deterioration from colonic stenting, as bowel function is preserved. Preoperative SEMS insertion should be considered only for patients with rectal or rectosigmoid junction cancer and patients for whom minimally invasive surgery is planned [10]. …”
mentioning
confidence: 99%